UM RELICTO LATINO EM CRUZ ALTA, RIO GRANDE DO SUL - Klassmann, Mario Silfredo (Organon, 2012)
A Latin palindrome was discovered in the ruins of Pompeii, wich was destroyed by an eruptionof the Vesuvius in the year 79AD. That palindrome reappeared in the town of Exaceter in the 4th century,during the Roman occupation of Britain. In 1992, in the district of Capão Grande, Cruz Alta, in the state ofRio Grande do Sul, an ALERS-Project researcher came across the same Latin palindrome. What makes thattext so remarkable as to have been preserved for such a long time in the popular culture of communities sodiverse and far removed in place and time? The present article intends to establish that relation.